An Enactive Approach to Learning Music Theory? Obstacles and Openings - Gutierrez, James (Frontiers in Education, 2019)
While music theory learning remains at the core of traditional music education, calls for more embodied and enactive approaches to music instruction rarely address theory pedagogy directly. This paper reconsiders theory teaching through a 4E lens, by (1) clarifying the obstacles presented by the legacy of Cartesian thought underlying conventional theory curricula, and (2) offering an original curricular tool that promotes embodied and enactive sense-making in an affordance-rich classroom environment. The tool is an adaptation of Conduction® –– a lexicon of signs and gestures created by jazz artist Butch Morris to be a flexible alternative to notation, allowing Morris to compose in real-time with an ensemble of any type, size, or background. In a theory-learning context, students bring their instruments to class, form an ensemble, and take turns using signs and gestures to conduct their peers, guided through processes aligned with learning objectives (ex. harmonic minor scales, Neapolitan chords, or polytonality), as well as to more freely experiment with musical structure in situ, with minimal or no reliance upon notation. Listening skills, structural knowledge, analytical proficiency, and performance technique are all enacted in the three roles students play: individual performer, ensemble member, and conductor. As students are placed in contact with the embodied metaphors that constitute the sense of musical structure, the cumulative effect is a deeply embodied sense of their musicality, and the identification of musical goals and theoretical strategies.